Cooperation in the Czech Republic border area on water management sustainability - Kročová, Šárka; Kavan, Štěpán (Elsevier SCI LTD, 2019)
The Czech Republic does not have a substantial source of surface water within its territorial catchment areas. Czech surface water is essentially divided and transported into the three seas in the European continent. This unchanging reality must permanently influence the Czech Republic’s water policy and principles of land use. Under new climatic conditions, water management must, among other things, consider wider international cooperation on water management within the European Union countries and agricultural land management. The aim of this paper is to characterize changes in water use and international solutions to water management issues that all are essential both for water management and the preservation of basic living conditions. The short-term failure of management solutions not only will increase the risk of water scarcity within the Czech Republic during the 21st century but at the same time may, in certain situations, cause many problems in water management and subsequently in the agricultural sector. The topic is further elaborated based on analysis, synthesis methods, expert reflection and literary research.
Spolupráce v příhraničním území České republiky z hlediska udržitelnosti hospodaření s vodami
Keywords: ecosystem; water scarcity; international cooperation; water management; agriculture; ekosystém; nedostatek vody; mezinárodní spolupráce; hospodaření s vodou; agriculture